Role of IT in Satisfying Human Needs of Faculty Members in Babasaheb Bhimrao Ambedkar University, Lucknow: a Case Study - Verma, Shilpi; Mahawar, K. L. (Journal of Information and Knowledge, 2010)
The paper covers the role of Information Technology in satisfying human needs of faculty of BBAU in particular. It provides a brief introduction and profile of BBAU. This focuses on various kinds of needs of faculty members and role of Information technology in satisfying the same such as cognitive needs, affection needs, etc. It also covers the factors which affect the information needs of faculty members in the university.